Seleksi Bakteri Asam Laktat dan Pemanfaatannya Sebagai Starter Kering Menggunakan Matriks Tapioka Asam - Ira Erdiandini; Titi Candra Sunarti; Anja Meryandini (Departemen Biologi, Institut Pertanian Bogor, 2015)
The development of industrial fermentation food could not separate with the availability of culture starter that suffice to support its production. Dried starter can be an option to use in fermentation industry because it can be stored for longer time without rejuvenation. However, in the process of production of dried starter needs the matrix to maintain cell viability, economically and availability of raw material. This research was conducted to use selected dried starter of indigenous lactic acid bacteria by using sour cassava starch matrix. Eleven local isolates lactic acid bacteria isolates from spontaneous fermentation of carbohydrates commodity were selected based on their acid production capabilities and antibiotics susceptibilities. Isolate of E 1222 showed the best result and was identified as Pediococcus pentosaceus. The isolate was encapsulated with sour cassava starch matrix for making dried starter by using freeze dryer and spray dryer. Freeze dried starter culture could maintained the cell viability higher than spray dried starter culture i.e 10.34 log CFU/g and 8.91 log CFU/g, respectively. Finally, freeze dried starter culture could maintain the percentage of cell viability until 89.38% during four-weeks storage at 4 oC.